2010
DOI: 10.1038/ejcn.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

Berry meals and risk factors associated with metabolic syndrome

Abstract: Background/Objectives: Nonalcoholic fatty liver disease is commonly associated with obesity, insulin resistance, dyslipidemia and type 2 diabetes, and can thus be regarded as the hepatic manifestation of metabolic syndrome. In this study we compared the effects of lifestyle intervention with and without industrial berry products, on risk factors associated with metabolic syndrome on slightly overweight women. Subjects/Methods: Sixty-one female volunteers (average age 42.9 years) were recruited and randomized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 37 publications
1
33
2
1
Order By: Relevance
“…According to a recent review, experimental and epidemiological studies have provided abundant evidence that adiponectin improves insulin sensitivity, and has potent antiatherosclerotic effects (Stefan and Stumvoll, 2002). In our earlier study adiponectin increased during mixed berry diet, although the difference between berry and lifestyle groups was not statistically significant (Lehtonen et al, 2010). In the present trial adiponectin was decreased more or less during all berry interventions.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…According to a recent review, experimental and epidemiological studies have provided abundant evidence that adiponectin improves insulin sensitivity, and has potent antiatherosclerotic effects (Stefan and Stumvoll, 2002). In our earlier study adiponectin increased during mixed berry diet, although the difference between berry and lifestyle groups was not statistically significant (Lehtonen et al, 2010). In the present trial adiponectin was decreased more or less during all berry interventions.…”
Section: Discussioncontrasting
confidence: 42%
“…Based on our earlier work (Lehtonen et al, 2010), 85 subjects formed the minimal size of study population needed to achieve sufficient statistical power. In the calculations, differences in the low-density lipoprotein cholesterol values between the intervention and the control groups were utilized.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it may influence the adipocyte function and increase c-reactive protein concentrations in plasma (McCarty, 2005). Sea buckthorn has been shown to reduce plasma c-reactive protein (Larmo et al, 2007) and a mixed berry diet enhanced liver function in our recent clinical trial (Lehtonen et al, 2010b). Meals that evoke high glycemic or insulinemic responses induce subsequent mild, late postprandial hypoglycemia and -insulinemia (Brand-Miller et al, 2002), resulting in a surge in adrenaline output (Ludwig et al, 1999) and inflammation mediator secretion (McCarty, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These results contrasted with those of an earlier study involving healthy young women consuming 750 mL/d of cranberry juice that showed no effects on blood antioxidant status or oxidative DNA damage [54], but the differences may have related to the study population, conditions of the test beverage, and outcome measures. Recent randomized clinical studies have related consumption of mixed berries (bilberries, lingonberries, strawberries, and black currants) to increased plasma concentrations of polyphenols and vitamin C, reduced blood pressure, increased HDL cholesterol, and inhibition of platelet function [55] and to reduced alanine aminotransferase levels as a marker of fatty liver-related inflammation in MetS [56]. Acute effects from berry meals are also detectable, as shown by a recent meal test study showing delayed and attenuated glycemic responses resulting from adding berries (black currants, bilberries, cranberries and strawberries) to a sugar load [57].…”
Section: Berries and Heart Healthmentioning
confidence: 99%